Analisis Penentuan Tarif Air Minum Pada Perusahaan Umum Daerah (PERUMDA) Air Minum Muara Tirta Kota Gorontalo - Ni Kadek Radha Sukertiyani; Mahdalena; Ronald S. Badu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the water tariff used to meet reasonable operational costs and whether it is reasonable or not, so that it can be considered or used as a reference for setting tariffs in the future. This research uses descriptive quantitative research methods. The data source uses primary data, namely financial report data and secondary data obtained from PERMENDAGRI and PERDA. The data analysis technique in this research is descriptive quantitative analysis using Break Event Point (BEP) calculations, Benefit Cost Ratio (BCR) and water tariff determination calculations based on PERMENDAGRI Number 21 of 2020. Based on the research results, it was found that Perumda Muara Tirta, Gorontalo City, from 2020 to 2022, experienced significant losses or fluctuations of IDR 48,797,510,675, IDR 46,464,848,896, and IDR 47,038,918,920. Based on the feasibility calculation for Perumda Muara Tirta's drinking water tariff, Gorontalo City using the Benefit Cost Ratio (BCR), the BCR value is 0.99, 0.98 and 0.91 or less than 1, which means the company experiences losses due to water tariffs that do not meet the criteri worthy.